The history of social psychology: Farr, Robert M (1996) The roots of modem social psychology, 1872-1954. Oxford Blackwell Publishers. Pp. xvii, 204. ISBN 0-631-19447-9. - Carson, John (PINS-Psychology in Society, 2026)
Why do psychological social psychology and sociological social psychology have so little to say to each other? Why has European social psychology, where it has withstood the onslaught, had so little impact on the dominant American-style of practice? And why is there so little of the social in social psychology? These are the questions that haunt Robert Farr’s The roots of modem social psychology. Clearly deeply unhappy with the current state of the discipline, Farr has fashioned a series of essays that seek to use history to suggest both how contemporary social psychology has come to be as it is, and how it might have been different It rs a tactic that makes for a curious book. As a work of pure history, The roots of modem social psychology is highly flawed, exhibiting few of the characteristics that one would expect of a piece of good historical scholarship And as a call to arms, it left at least this reader (admittedly an historian rather than a social psychologist) a bit at sea, wondering whether rewriting the history of a discipline is the most efficacious way in which to reform its current practice.